Pyrolysis of coal group component. Part Ⅰ. Emission characteristics and product distribution of saturate component. (1st February 2021) - Jiang, Yuan; Zong, Peijie; Tian, Bin; Ming, Xue; Xu, Fanfan; Tian, Yuanyu; Qiao, Yingyun; Li, Dawei; Song, Qingshuo; Yu, Qiankun
Abstract: Studying pyrolysis behavior of saturate component is significant to understand the pyrolysis behaviors of coal, as the component can produce volatile matters. The combined utilization of TG-FTIR and Py-GC/MS provides a feasible strategy for investigating pyrolysis behaviors of saturate component. The results of TG-FTIR show that the pyrolysis of saturate component contains one stage. The yield of coal-char at different heating rates is quite low (0.04–0.50 wt%) and the values are close to each other, which indicates that the pyrolysis of saturate component has almost no coal-char and the saturate component mainly consists of volatile substances. Furthermore, the change in absorbance of typical compounds in FTIR indirectly reflects the variety in the content of compounds. The detailed information of pyrolysis products is analyzed by Py-GC/MS, which shows that alkanes and alkenes are dominant. Moreover, the change in the content of alkanes and alkenes is opposite. The pyrolysis mechanism of saturate component belongs to free radical reaction. The possible pyrolysis pathway of saturate component is presented and the appearance of hexane and hexene is also verified. This research provides a methodological model for exploring other group components and reveals more specific details for the pyrolysis of coal. Highlights: The pyrolysis of saturate component contains one stage and almost no coke is formed. The delayed effect of heating rate on characteristic temperature weakens. The releasing characteristics of volatiles is consistent with pyrolysis behavior. Alkanes and alkenes are the main pyrolysis products of saturate component. The pyrolysis mechanism of saturate component is free radical mechanism.